Pengaruh Produk Domestik Bruto (Pdrb) Dan Pengangguran Terhadap Indeks Pembangunan Manusia Di Provinsi Sumatera Selatan Pada Tahun 2017 – 2021 - Misfi Laili Rohmi; Agnes Alfi Normadila; Afdhol Dinil Haq (Akuntansi dan Ekonomi Pajak: Perspektif Global, 2024)
All people certainly really want a peaceful and prosperous life, but in reality it is not that easy to get a decent life, there are many factors that become challenges such as the low human development index, very high unemployment rates and the problem of poverty which has mushroomed in various regions. . Poverty is also described as the most complex social problem, so it must always receive special attention from the government. This study uses quantitative methods and uses secondary data obtained from the Central Statistics Agency of South Sumatra Province, using time series data from 2017-2021. The aim of this research is to determine the influence of GRDP and unemployment on HDI in South Sumatra Province. Data analysis was carried out using a multiple linear regression analysis test, the results of which showed that GRDP and unemployment simultaneously had a significant influence on the HDI percentage. Partially, GRDP does not have a significant influence, while the unemployment variable has a significant influence on the Human Development Index in South Sumatra Province in the 2017-2021 period.